2019
DOI: 10.1055/s-0039-1695783
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Intensive Care Unit-Acquired Pneumonia

Michael Klompas

Abstract: Intensive care unit (ICU) acquired pneumonia is one of the most common and morbid health care-associated infections. Despite decades of work developing and testing prevention strategies, ICU-acquired pneumonia remains stubbornly pervasive. Pneumonia prevention studies are difficult to interpret because all are at risk of bias due to the subjectivity and poor specificity of pneumonia definitions. Interventions associated with improvements in objective outcomes in addition to pneumonia, such as length of stay or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 113 publications
(132 reference statements)
0
16
0
4
Order By: Relevance
“…Recent studies also con rmed the effectiveness of the VAP prophylaxis package [14,15] . We found that most of these measures were related to nursing [16] .Our survey found that nurse sta ng and nursing practices affect the incidence of ventilator-associated pneumonia ( Table 5). The ndings are that the incidence of VAP had a positive relationship with the proportion of nurses who had worked less than 5 years and the number of patients that nurses care for on the night shift.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies also con rmed the effectiveness of the VAP prophylaxis package [14,15] . We found that most of these measures were related to nursing [16] .Our survey found that nurse sta ng and nursing practices affect the incidence of ventilator-associated pneumonia ( Table 5). The ndings are that the incidence of VAP had a positive relationship with the proportion of nurses who had worked less than 5 years and the number of patients that nurses care for on the night shift.…”
Section: Discussionmentioning
confidence: 83%
“…Registro identificado no banco de dados de busca (Pubmed (pneumonia) AND (oral health)) AND (dental biofilm)) AND (intensive care unit) -n = 3 (1) Klompas, 2019 Seminars in Respiratory and Critical Care Medicine…”
Section: Inclusãomentioning
confidence: 99%
“…To prevent these complications, oral care with chlorhexidine have been used. However, a recent systematic review concluded that it is best, for now, to avoid using chlorhexidine in this case given the absence of clear evidence of benefit and the possible suggestion of harm (potentiate the development of intensive care unit-acquired pneumonia) [43].…”
Section: The Effects Of Covid-19 Treatment On Oral Healthmentioning
confidence: 99%